The Use of Principle Component Analysis in Type Classification of Air-dry Peat; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Chukhareva N. V. Natalia Vyacheslavovna (Comprehensive Utilization of Mineral Resources, 2014)
Title screen